Impact of Doublesynch and Ovsynch Protocols, Preovulatory Follicle, Estradiol and Luteal Profiles on Fertility in Cyclic Murrah Buffaloes during Breeding and Compromised-Breeding Season - Kumar, Parveen; Pandey, Anand Kumar; Kumar, Sandeep; Pradeep,; Saini, Gitesh; Hitesh,; Singh, Gyan (The Indian Journal of Animal Reproduction, 2022)
The present study designed to evaluate the efficacy of Doublesynch and Ovsynch estrus synchronization protocols, preovulatory follicle (POF) and luteal profile in cyclic Murrah buffaloes (n=83) in summer and winter season at farm and field level. In Ovsynch protocol, buffaloes were administered (i.m.) two injections of 10µg, Buserelin acetate on days 0 and 9, and an injection of 500µg, Cloprostenol on day 7. In Doublesynch protocol, an additional injection (i.m.) of 500µg, Cloprostenol 2 days before the start of Ovsynch protocol was administered. The ultrasonography (USG) and blood sampling was performed on each day of treatment, on day of estrus and 10 days post-AI. The conception rate in Ovsynch treatment group during summer and winter season was 20% and 27.8%, respectively and in Doublesynch groups, it was 40% and 48% in summer and winter season, respectively. Overall mean diameter of POF on day of estrus was larger (p
Keywords: Conception rate; Murrah buffalo; Ovsynch; PGF2α; POF